Artificial Intelligence in Accounting: Assessment of the Current State - Karolina SZKUDLAREK (Communications of International Proceedings, 2025)
The purpose of the article is the assessment of the current state of AI implementation in accounting.  New technologies are very important part of modern life. Their implementation has undoubtedly advantages, but on the other hand it raises many doubts. Artificial Intelligence (AI) is considered to be one of the most controversial. Artificial intelligence is increasingly being adopted within the accounting profession. However, numerous issues still require regulatory oversight, encompassing not only technical aspects but also ethical and legal considerations.
Keywords: Artificial Intelligence; new technologies; regulations for AI; AI in accounting